NATURALIZATION OF THE FOREIGN ATHLETE A COMPARATIVE STUDY OF IRAQI, EMIRATI, FRENCH AND SOUTH KOREAN LEGISLATION. - M.D. Mohammed TaherQasim AL-Awjar, Prof. RaadMiqdadMahmood (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Naturalization in general is the person’s acquisition of a nationality that is proven to him after birth, even if some of the elements of acquiring it after birth, as the lesson is to fully enter into the nationality and to what extent this was achieved at the time of birth or at a later date. The acquired nationality differs from the original nationality in terms of the time it was acquired, and what unites them is the need for a link between the individual and the state granting the nationality. The nationality laws that are the subject of comparison in the research did not agree on a specific formula that defines the legal nature of the naturalization of a foreign athlete, and the most likely opinion is that the naturalization of a foreign athlete is naturalization based on the performance of a useful service for the country as stipulated in some of the nationality laws in question, such as the Iraqi, Emirati and French laws. And South Korean. The naturalization of foreign athletes is one of the topics of newly established and rapidly formed, so countries that interested in sports activity and their desire to develop their various sports activities have tended to naturalize foreign athletes so that these people can represent this country (nationality grantor) in regional and international activities and tournaments to achieve sporting achievements in this regard. , Explicit laws legislated and regulated the various types of naturalization, including the naturalization of the foreign athlete under different legal names and situations, some countries considered the naturalization of the foreign athlete in exchange for providing useful or great services to the state, and others made it an exception to the general rule of naturalization and this is what we will address in the research subject of study.